The strains produced by precipitation in alloys - Nabarro, F.R.N. (Royal Society of London, 1940)
If the process in metals results simply in the interchange of pairs of atoms large strains must be set up when a new phase prcipitates in an alloy. The strain energy involved is calculated for particles of precipitate of various shapes, and is found to be least if the precipitate forms thin plates. The shape of the particle actually formed is influenced by this energy, by the degree of supersaturation of the solid solution, and by surface effects; the calculated shape is shown to agree reasonably well with that observed experimentally.
Keywords: precipitation in alloys; alloys